التوجيه الدلالي للتحويل بحذف الفعل مقاربة تحويلية - مغناجي, محمد (University of Eloued جامعة الوادي, 2016)
يحاول المقال البحث في قضية التحويل بحذف الفعل من الجملة في اللغة العربية، وفق مقاربة تحويلية للوصول إلى التوجيهات الدلالية التي يحققها حذف الفعل في الجملة في اللغة العربية، والدراسة كانت في ربع مريم من القرآن الكريم. The article tries to look at the issue of conversion to delete the verb of the sentence in Arabic, according to a transformative approach to reach Remember guidance achieved by deletion of the verb in the sentence in the Arabic language, and the study was Mary(maryam) in the quarer from the Koran.
Keywords: التوجه الدلالي، اللغة العربية، الجملة; Semantic orientation, Arabic language, sentence